(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The study’s goal is to learn more about the use of ICT at the University Library in M.P. and thepart that local, regional, national, and international organizations play in encouraging and facilitating thistrend. The library services have been enhanced to the greatest extent feasible thanks to the availabilityof infrastructure at individual libraries for the deployment of IT. With the acquisition of cutting-edgeapplication technologies, the academic sector is giving a growing number of activities greater priorities.Some people have taken the use of IT seriously, while others are beginning to show interest in it. Public,academic, and special libraries all make use of information and communication technology (ICT), butresearchers have made just a few attempts to compare and contrast these uses. To our knowledge, noresearch has been conducted on the effects of ICT on university libraries in M.P. or on the creation of anappropriate model for an integrated university library and information system in response to theseneeds. With this research, we make an effort in that general course. The instruments of information andcommunication technology have become indispensable to modern society. They use the internet to carryout their surveys and look for information to help them achieve their aims. Integrating libraries arecurrently able to help their patrons more effectively achieve their objectives. They’ll get annoyed if youtreat them like the ineffective, uninterested salespeople you’d find at a large shopping center.Consequently, interconnected libraries make it easier for scholars anywhere to access the knowledgethey need, and for the academic community as a whole to achieve its goals in the most effective, reliable,and predictable way possible. After a positive experience, they will return to the libraries for furtherresearch and will likely tell their peers about the Integrate libraries they found most useful. In time, theselibraries provide their communities with a treasure trove of information.